An Airfield Soil Pavement Design Method Based on Rut Depth and Cumulative Fatigue - Duoyao Zhang; Liangcai Cai; Shaohui Zhou (Journal of Advanced Transportation)
The structure and damage modes of soil pavement, as well as existing problems in current design methods, were comprehensively analyzed, and a new design method for airfield soil pavement was proposed. The proposed method avoids the use of the “designed aircraft” concept and instead adopts the cumulative fatigue theory widely used in permanent airfield design at present. Moreover, in view of the lack of aircraft wheel trajectory distribution data, an approximate method for calculating the wheel trajectory distribution considering the side slip distance of the aircraft was proposed and the equivalent width of the wheel tread was calculated by introducing the modulus ratio. Finally, the pass-to-coverage ratio was obtained. According to the characteristics and damage modes of airfield soil pavement, rut depth was determined to be the unique factor affecting soil pavement damage, and resilient modulus was used as the control variable to improve the adverse impact of the empirical method. Furthermore, according to the rut prediction formula for airfield soil pavement put forward by the US Army Engineer Research and Development Center, a fatigue equation based on the resilient modulus was proposed to calculate the allowable number of repetitions. To verify the reliability of the design method, a test section was constructed at a test center in Jining, China, and the theoretical maximum allowable repetitions on the soil runway were calculated by the currently used California bearing ratio test, the β-fatigue equation, and the proposed method. Aircraft traffic tests were carried out on the test section. Finally, the theoretical and test results were compared and the values calculated via the proposed method were found to be consistent with experimental values, thereby validating the reliability of the method.